The practice of diaspora : literature, translation, and the rise of Black internationalism - Edwards, Brent Hayes (Harvard University Press, 2003)
Brent Edwards revisits black transnational culture in the 1920's & 1930's, paying particular attention to links between intellectuals in New York & their Francophone counterparts in Paris. He argues that diaspora is less a historical condition than a set of practices.